Pelatihan media pembelajaran berbasis digital bagi guru di SMPN 1 Rantau Selamat Aceh Timur - Prima Nucifera; Muhammad Yakob; Setyoko Setyoko (Universitas Hamzanwadi, 2022)
Information and communication technology development continues to proliferate, and teachers must continue to learn using various digital-based learning media. Training on using digital media for teachers will encourage teachers to create digital media needed during classroom learning. Community service (PKM) through digital-based learning media training for teachers at SMPN 1 Rantau Selamat, East Aceh. This activity aims to provide training in making digital-based media, such as digital books (e-books) and digital comics. The training participants were 20 teachers representing each subject area. PKM activity methods are (1) Dissemination of digital media training, (2) Preparation of technology devices, (3) Digital Media Training, and (4) Training Monitoring and Evaluation. As a result of this training activity, participating teachers at SMPN 1 Rantau Selamat have 20 digital-based learning media products, namely e-books or digital comics, for each subject. The teacher will later implement this digital media in learning activities in the odd semester of the 2022/2023 school year. This PKM program increases teacher competence in developing digital-based learning media.